Exploiting the dual role of ethynylbenziodoxolones in gold-catalyzed C(sp)-C(sp) cross-coupling reactions - Banerjee, Somsuvra; Patil, Nitin T. (Chemical Communications, 2017)
Reported herein is the gold-catalyzed alkynylation of terminal alkynes using ethynylbenziodoxolones (EBXs), where EBXs serve a dual role as oxidants as well as alkyne transfer agents to access unsymmetrical 1,3-diynes. Hence, the catalytic system requires no external oxidants and is compatible with a broad range of substrates, including those with polar functional groups such as NH, OHand B(OH)(2).